PENGARUH PERTUMBUHAN EKONOMI, PENDAPATAN ASLI DAERAH, DAN PENGELUARAN PEMERINTAH TERHADAP KEMISKINAN KABUPATEN/KOTA DI KALIMANTAN BARAT - B2051132012, ERNI (Jurnal Ekonomi Daerah (JEDA), 2016)
The background of this research are economic growth, Region Own-Source Revenue, and Government Expenditure and Poverty. The aims of this study are to examine the effect of Economic Growth, Region Own-Source Revenue, and Government Expenditure towards Poverty in West Kalimantan. The GLS (Generalized Least Square) method of Multiple Regression is used to examine the hypothesis. The research findings are region own-source revenue significantly affect poverty, except economic growth and government expenditure. The local revenue (so called PAD) is derived from local revenue sources of local economies that are not tied to the other party. PAD high with the Local Government have sufficient funds to finance government affairs and regional development. The Local Governments should encourage public awareness of paying taxes to improve the quality of public service facilities as well as the ease of tax payment process. The economic growth should be contribute to poverty reduction, so the government needs to develop agricultural product processing industry to create alternative jobs are more qualified and can provide added value and revenue greater community. This policy needs to be supported by improving the quality and quantity of road infrastructure so it can open up access between regions. The need for analysis of the development of regional revenue allocation districts / cities in West Kalimantan so that we can determine the extent of regional revenue is used for programs and activities that can reduce poverty . Economic growth and government spending should also be analyzed more deeply, so that it can make a positive contribution in reducing poverty in the province of West Kalimantan Keywords : Poverty,Â  Economic Growth , Local Revenue , Government Expenditure